PERAN LEMBAGA KEUANGAN SYARIAH DALAM MENGIMPLEMENTASIKAN AKAD MUDHARABAH - Muflih, Muflihatul Fauza (AL-IQTISHAD : Jurnal Perbankan Syariah dan Ekonomi Islam, 2023)
The problem in this paper that we want to study is related to the implementation of sharia financial institutions' mudharabah agreements when they are in the position of amil. In reality, sharia financial institutions do not carry out real business activities, but throw back the capital they receive to other parties or third parties, so how is the mudharabah agreement implemented in sharia financial institutions? The method used is descriptive qualitative. By describing descriptively what is obtained from books and journals. As for the results of the problem, it can be described that legally a sharia financial institution with its capacity as the first 'amil is allowed to enter into mudharabah contracts with other parties (entrepreneurs), so that its capacity changes to become the second rab al-mal. However, this ability is only legally justified if the 'amil's actions are permitted by the first rab al-mal.